Perbandingan Induk Jantan Dan Betina Terhadap Keberhasilan Pembuahan Dan Daya Tetas Telur Ikan Jelawat (Leptobarbus Hoevenii) - Anny Rimalia (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2014)
For the success rate of fertilization and hatching rate of fish eggs Jelawat required amount sufficient sperm for fertilization. This study uses completely randomized design 3X3, with treatment A comparison of the male parent female 2 : 1, treatment B male parent female ratio of 3: 1 and the treatment of male female parent comparisons C 4 : 1. The results of the fertilization rate of eggs produced fish Jelawat best treatment C ( 96.37 % ) with the ratio of male parent female 4 : Power Level 1 and hatching fish eggs produced Jelawat best treatment B ( 94.33 % ) in the ratio of male parent female 3 : 1.Results of all water quality parameters indicate conditions for hatching fish eggs support for Jelawat, but for ammonia concentrations slightly above the recommended value